Effectiveness of Implementing Occupational Nutrition for Government Agency Employees' in Jambi City - Budi Aswin; Ismi Nurwaqiah Ibnu; La Ode Reskiaddin (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Fulfillment of nutrition for workers can affect their level of health and work productivity. If nutritional needs are not met, it can have negative impacts on the body, such as work fatigue, decreased productivity, and decreased concentration. Aims of this study is to analyze the effectiveness of the implementation of work nutrition among government agency employees' in Jambi City. This research was conducted in Jambi City, especially at the Jambi City Public Works and Spatial Planning Service and the Jambi City Manpower, Cooperatives, and SMEs Service, which took place in April-October 2023 with a sample size of 58 respondents. Data were analyzed using the Mann-Whitney test with α = 0.05. There were two intervention groups; the first group underwent intervention by providing occupational nutrition modules and mobile phone intervention, while group 2 was the control group. he results of the analysis showed no difference in diet (p = 0.926) or physical activity (p = 0.243) between intervention group and control group employees'. There were differences in safety behavior (p = 0.037), attitudes (p = 0.018), and motivation related to occupational nutrition (p = <0.001) between intervention group employees' and control groups of government agency employees' in Jambi City. In conclusion, the occupational nutrition package was not effective in improving the diet and physical activity of employees'. The work nutrition package is effective in improving knowledge, safety behavior, attitudes, and motivation related to work nutrition among employees' of government agencies in Jambi City. Keyword : Effectiveness, Government Employees', Job Nutrition